2021
DOI: 10.2147/cmar.s292342
|View full text |Cite
|
Sign up to set email alerts
|

Novel Resistance Mechanisms to Osimertinib Analysed by Whole-Exome Sequencing in Non-Small Cell Lung Cancer

Abstract: Purpose Molecular-based targeted therapy has improved life expectancy for advanced non-small cell lung cancer (NSCLC). However, it does not have to be inevitable that patients receiving third-generation EGFR-TKIs become drug resistant. EGFR C797S and MET amplification are common mechanisms of osimertinib. However, a large part of these potential drug mechanisms remains unknown, and further research is needed. Methods Tumour and blood samples from forty advanced NSCLC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Osimertinib is a relatively specific inhibitor of mutant active forms of ERBB1 and is, at present, the standard of care therapeutic. As with all targeted drugs in cancer, eventually NSCLC cells become osimertinib resistant, with diverse mechanisms, including gain of additional ERBB1 mutations or activation of other receptor tyrosine kinases such as c-MET and FGFRs (15)(16)(17)(18). Overcoming osimertinib resistance remains an important area for the developmental cancer therapeutics field in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Osimertinib is a relatively specific inhibitor of mutant active forms of ERBB1 and is, at present, the standard of care therapeutic. As with all targeted drugs in cancer, eventually NSCLC cells become osimertinib resistant, with diverse mechanisms, including gain of additional ERBB1 mutations or activation of other receptor tyrosine kinases such as c-MET and FGFRs (15)(16)(17)(18). Overcoming osimertinib resistance remains an important area for the developmental cancer therapeutics field in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, EGFR is related to pulmonary inflammation and its phosphorylation can regulate the expression of pro-inflammatory factors, such as IL-8 and CXCL1 35 , 36 . EGFR also activates multiple signaling pathways, such as PI3K/Akt/mTOR, JAK/STAT and NF-κB, which are closely related to inflammation 37 . LCK, a cytoplasmic tyrosine kinase expressed in T cells and natural killer cells, is a necessary step to activate T cell.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of gene expression profiles has also reported MuD-dependent upregulation of SOS2 expression in cohorts of TCGA glioblastomas (GBM), and a correlation between high expression of the two genes and longer survival of proneural GBM patients [ 67 ]. Finally, a whole-exome sequencing analysis carried out on non-small cell lung cancer samples demonstrated a direct correlation between SOS2 and resistance mechanisms to Osimertinib [ 38 ].…”
Section: Sos2 Functional Role(s) In Pathological Contextsmentioning
confidence: 99%
“…In this regard, a significant number of gain-of-function SOS1 mutations (and, more rarely, SOS2 mutations), resulting in subsequent hyperactivation of RAS signaling, have been identified in inherited RASopathies, such as Noonan syndrome (NS) or hereditary gingival fibromatosis, as well as in various sporadic human cancers, including endometrial tumors and lung adenocarcinoma, among others [ 5 ]. However, during the last few years, a previously undetected but relevant involvement of SOS2 in some of these pathologies is also coming to light in a series of studies describing specific SOS2 gene alterations that have been identified in several forms of cancers and RASopathies, as well as the potential therapeutic effect of explicit SOS2 removal in certain tumor cell lines [ 36 , 37 , 38 , 39 , 40 ]. All in all, these observations and the above-described timeline of experimental evidence support the notion that, besides SOS1, SOS2 may also constitute a worthy therapy target for prevention and/or treatment of some specific tumor and nontumor pathologies with epidermal origin or dysregulated PI3K/AKT signal transmission [ 25 ].…”
Section: Sos2 Vs Sos1 Function: An Introductory Timeline Perspectivementioning
confidence: 99%